APLIKASI PUPUK PELENGKAP CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (Brassicajuncea L.) - Suparman '; Husna Yetti; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aims to determine the concentration of complement liquid fertilizer to support the growth and yield of mustard. The research was conducted at the Experimental Faculty of Agriculture, University of Riau from April 2014 through May 2014. Research was conducted using a Completely Randomized Design with 5 treatments and 4 replications. The concentration of complementary liquid fertilizer treatment given is B0 (0 ml/l of water) (control), B1 (1 ml/l of water), B2 (2 ml/l of water), B3 (3 ml/l of water), B4 (4 ml/l of water).The parameters measuredwere plant height (cm), number of leaves (blade), leaf area (cm2), weight fresh plants and fresh weight worth of consumption. The results showed that administration of supplementary liquid fertilizer could increase the growth and yield of mustard. The complementary liquid fertilizer at a concentration of 4 ml/l of water was the recommended concentration on the research that has been conducted for all test parameters Keyword :Complementary liquid fertilizer, Mustard plant,Brassica juncea L.